Optimasi Proses Load Aplikasi HDD Pada SO Windows Dengan Prefetch Files - Agustinus Suradi; Doni Setyawan (Jurnal Informatika: Jurnal Pengembangan IT, 2018)
In the current era with the help of IT devices can be done more quickly, effectively and efficiently. Good collaboration between brainware, software and hardware, will produce the expected work performance and response. The Windows operating system, when loading applications, analyzes the files used during startup and what applications are running, then create index files and save them in HDD. With the Windows index can load applications faster. Windows 7 will crack the activity, and the mapping will be reused while loading the HDD app so it will speed up system performance, try to load this application by using 3 prefetch files network method by disabling prefetch, clear prefetch and prefetch activation. Recording time required in HDD application load on Windows operating system with Prefetch Files, in a WMPLAYER.EXE application with 61,800 milliseconds, WORDPAD.EXE record time of 77,367 milliseconds, and CHROME.EXE with the record time of 904,400 milliseconds. Pada Using Prefetch Files then the load time of the HDD app will be faster than without using Prefetch Files or by removing Prefetch Files.